Crystal growth principles, methods, properties of silicon carbide and its new process prepared from silicon cutting waste - Shengqian Zhang; Yongsheng Ren; Xingwei Yang; Wenhui Ma; Hui Chen; Guoqiang Lv; Yun Lei; Yi Zeng; Zhengxing Wang; Bingxi Yu (Journal of Materials Research and Technology)
The third-generation semiconductor silicon carbide (SiC) has attracted widespread attention due to its excellent properties, such as high thermal conductivity, large bandgap, high breakdown field strength, and high saturation electronic drift rate, etc. Consequently, the growth process, physical structure, and properties of SiC crystals have also become research hotspots in industry and academia sectors. With the concept of carbon peak and carbon neutrality, the photovoltaic industry has witnessed rapid development. In the process of silicon wafer production, nearly half of the crystalline silicon is lost in the form of silicon powder into silicon cutting waste (SCW), which results in a great waste of resources and severe environmental pollution, and therefore the use of SCW for the preparation of SiC materials has received great attention in recent years. This paper highlights the principles and methods of SiC growth, crystal structure and properties, and discusses the application of SiC prepared from SCW.